The Islamic Concept of Education Reconsidered - Khosrow Bagheri (International Institute of Islamic Thought, 2006)
Some authors have analyzed the Islamic concept of education in parallel to the assumed contrast between Islam and the liberal tradition. Hence, given the latter’s rationalist tendencies, an almost indoctrinatory essence is assumed for the Islamic concept of education. However, we argue that rationality is involved in all elements of the Islamic concept of education. There might be some differences between the Islamic and liberal conceptions of rationality, but these are not so sharp that the derivative Islamic concept of education can be equated with indoctrination. We suggest an Islamic concept of education that includes three basic elements: knowledge, choice, and action. Then, we show that, according to the Islamic texts, these elements have a background of wisdom.